PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KEPUASAN PELANGGAN INFORMA SAMARINDA SQUARE - Rafenni Pasonggo (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This study aims to determine the effect of Total Quality Management (TQM) Implementation on Informa Samarinda Square Customer Satisfaction, Samarinda either partially or simultaneously. This research uses a quantitative approach. The population and samples used by the researchers were consumers who were visiting Informa Samarinda Square Samarinda which numbered 100 respondents. The data collection in this study used questionnaires. Data analysis tools used validity test, reliability test, classic assumption test, multiple linear regression test, determination coefficient test, F test and T test. From this study it was concluded that there is a strong positive relationship between variable focus on customers (X1), obsession with quality (X2), teamwork (X3), andemployee engagement and empowerment (X4), to customer satisfaction (Y). This is evidenced by the correlation coefficient value of r 0.696 or 6.96%. The results of this study concluded that customer focus variables (X1), obsession with quality (X2), teamwork (X3), andemployee engagement and empowerment (X4), partially had a significant effect on customer satisfaction (Y). This is evidenced by the t calculated value of 9,605 with a significant rate of 0.000 < 0.05.